Do "they" threaten "us" or do "we" disrespect "them": Majority perceptions of intergroup relations and everyday contacts with immigrant minorities. (September 2014) - Van Acker, Kaat; Phalet, Karen; Deleersnyder, Jozefien; Mesquita, Batja
The present study examined how majority perceptions of intergroup relations afford different contact experiences with immigrant minorities. Majority students attending culturally diverse high schools first completed a survey that measured the extent to which they perceived immigrant minorities as either threatening to the majority or discriminated by the majority. Two weeks later, the same majority students kept a 1-week diary of their contacts with immigrant minorities. As expected, perceived threat at premeasurement was positively associated with situated threat-related appraisals and emotions (e.g., fear) during everyday contacts with immigrant minorities 2–3 weeks later. In contrast, acknowledgment of discrimination at premeasurement was positively associated with perspective taking and enrichment-related appraisals and emotions (e.g., admiration). These findings suggest that generalized threat perceptions can become self-enforcing through repeated threatening contact experiences; but also that an alternative perception of minorities as disrespected by the majority may underlie more positive contact experiences.